Seroprevalence of Toxoplasma gondii, Neospora caninum and Trichinella spp. in Pigs from Cairo, Egypt - Ragab M. Fereig; El-Sayed El-Alfy; Hanan H. Abdelbaky; Nour H. Abdel-Hamid; Amira M. Mazeed; Ahmed M. S. Menshawy; Mohamed A. Kelany; Mohamed El-Diasty; Bader S. Alawfi; Caroline F. Frey (Veterinary Sciences, 2023)
Pork production is a niche economy in Egypt, and pigs are typically raised as backyard animals with no sanitary control, potentially exposing them to various pathogens. Commercially available ELISAs were used to detect specific antibodies to the food-borne zoonotic parasites Toxoplasma gondii and Trichinella spp., as well as to Neospora caninum, in serum samples of pigs slaughtered at Egypt’s only licensed pig abattoir, the El-Bassatin abattoir in Cairo. Among the tested sera (n = 332), seroreactivity for T. gondii was 45.8% (95% confidence interval: 40.4–51.3), N. caninum was 28.0% (95% CI: 23.3–33.2), and Trichinella spp. was 1.2% (95% CI: 0.4–3.3). Mixed infection was only detected for T. gondii and N. caninum (18.7%; 95% CI: 14.7–23.4). The seroprevalence of T. gondii was significantly higher (p = 0.0003) in animals collected from southern Cairo (15 May city slum) than in eastern Cairo (Ezbet El Nakhl slum). Seroprevalence for N. caninum was higher in western (Manshiyat Naser slum; p = 0.0003) and southern Cairo (15 May city slum; p = 0.0003) than in that of eastern Cairo (Ezbet El Nakhl slum; p = 0.0003). Moreover, female pigs exhibited a higher rate of N. caninum antibodies than male ones (p < 0.0001). This study provides the first seroprevalence data for N. caninum in pigs in Egypt, and updates the prevalence of the zoonotic parasites Trichinella spp. and T. gondii.